(untitled) (Pesquisa Odontológica Brasileira, 2002)
Considering the current context of increasing and early utilization of licit or illicit drugs (habit-forming substances), the aim of this study was to evaluate the oral health conditions of 102 males from the Esquadrão da Vida rehabilitation center, in Bauru, São Paulo, Brazil. The evaluation was carried out by means of the assessment of caries experience (DMFT), dental plaque (PHP), gingival index and salivary flow. This study also aimed at instituting an educational-preventive program and evaluating its efficacy. The subjects mean age was 29.17 years (sd = 11.40; n = 95). From all subjects (n = 102), 72.54% had the habit of eating between meals, and 69.60% did not utilize dental floss. The observed DMFT was 14.88 (sd = 6.38; n = 86). The initial PHP was 2.34 (sd = 0.69; n = 14) and, after 3 months, it was reduced to 1.91 (sd = 0.74; n = 14). The initial salivary flow was 1.31 ml/min (sd = 0.7; n = 97). Due to the fluctuation of this group, only 13 of the original subjects were reevaluated after 3 months, when a salivary flow of 1.13 ml/min (sd = 0.49) was registered. The initial gingival index and PHP presented r = 0.30 (p = 0.002 - statistically significant). The objective need for treatment and the subjective importance given to oral health were negatively correlated (r = -0.26; p = 0.019 - statistically significant), which indicates that the value attributed to oral health influences health care and affects the oral health-sickness process.